2020
DOI: 10.31124/advance.12800663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

#ForYou: The User’s Perspective on How TikTok Recommends Videos

Abstract: <p>This study focuses on the contradiction between the alleged inclusivity and diversity that TikTok promotes and its apparent indifference for ethical standards. Specifically, the goal is to explore how post-Millennials (those born after 2000) perceive TikTok and how they adopt moral rationalizations to reconcile ethical and moral conflicts. Relatively little research has focused on young people’s moral reasoning in social media and no study to date has provided the opportunity to voice a user’s own exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interviews lasted for 45-60 min and were semi-structured with open-ended questions. An interview protocol with a list of discussion points was written beforehand (Scalvini, 2020a: Appendix 1). To promote a culture of open scientific inquiry, the present study recognizes the value of open data for discouraging research fraud and permitting critical scrutiny.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews lasted for 45-60 min and were semi-structured with open-ended questions. An interview protocol with a list of discussion points was written beforehand (Scalvini, 2020a: Appendix 1). To promote a culture of open scientific inquiry, the present study recognizes the value of open data for discouraging research fraud and permitting critical scrutiny.…”
Section: Methodsmentioning
confidence: 99%
“…To promote a culture of open scientific inquiry, the present study recognizes the value of open data for discouraging research fraud and permitting critical scrutiny. For this reason, the repository of the anonymized transcripts is deposited on Harvard Dataverse (Scalvini, 2020a) in Refi-QDA format. Certainly, the goal is to increase accountability and transparency, but also to encourage a new practice of open data in qualitative research by maximizing the value of the interviewees' contributions and increasing diversity in analysis and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, short video marketing is capable of capturing the audience. Studies have shown that nearly all the audiences, despite their various emotional characteristics, will choose to use short video entertainment continuously [12], because short videos can bring them a sense of selfactualization [13] and social identity. Although they are fully aware that they are prone to overuse [14], they are always the weaker side in the mutual dependence relationship [15].…”
Section: Sustainable Communication Marketingmentioning
confidence: 99%